Genome Assembly and Sex-Determining Region of Male and Female Populus × sibirica - Melnikova, Nataliya V.; Pushkova, Elena N.; Dvorianinova, Ekaterina M.; Beniaminov, Artemy D.; Novakovskiy, Roman O.; Povkhova, Liubov V.; Bolsheva, Nadezhda L.; Snezhkina, Anastasiya V.; Kudryavtseva, Anna V.; Krasnov, George S.; Dmitriev, Alexey A. (Frontiers in Plant Science, 2021)
The genus Populus is presented by dioecious species, and it became a promising object to study the genetics of sex in plants. In this work, genomes of male and female Populus × sibirica individuals were sequenced for the first time. To achieve high-quality genome assemblies, we used Oxford Nanopore Technologies and Illumina platforms. A protocol for the isolation of long and pure DNA from young poplar leaves was developed, which enabled us to obtain 31 Gb (N50 = 21 kb) for the male poplar and 23 Gb (N50 = 24 kb) for the female one using the MinION sequencer. Genome assembly was performed with different tools, and Canu provided the most complete and accurate assemblies with a length of 818 Mb (N50 = 1.5 Mb) for the male poplar and 816 Mb (N50 = 0.5 Mb) for the female one. After polishing with Racon and Medaka (Nanopore reads) and then with POLCA (Illumina reads), assembly completeness was 98.45% (87.48% duplicated) for the male and 98.20% (76.77% duplicated) for the female according to BUSCO (benchmarking universal single-copy orthologs). A high proportion of duplicated BUSCO and the increased genome size (about 300 Mb above the expected) pointed at the separation of haplotypes in a large part of male and female genomes of P. × sibirica. Due to this, we were able to identify two haplotypes of the sex-determining region (SDR) in both assemblies; and one of these four SDR haplotypes, in the male genome, contained partial repeats of the ARR17 gene (Y haplotype), while the rest three did not (X haplotypes). The analysis of the male P. × sibirica SDR suggested that the Y haplotype originated from P. nigra, while the X haplotype is close to P. trichocarpa and P. balsamifera species. Moreover, we revealed a Populus-specific repeat that could be involved in translocation of the ARR17 gene or its part to the SDR of P. × sibirica and other Populus species. The obtained results expand our knowledge on SDR features in the genus Populus and poplar phylogeny.